Urban Legends and Paranormal Beliefs: The Role of Reality Testing and Schizotypy - Dagnall, Neil; Denovan, Andrew; Drinkwater, Kenneth; Parker, Andrew; Clough, Peter J. (Frontiers in Psychology, 2017)
Recent research suggests that unconventional beliefs are locatable within a generic anomalous belief category. This notion derives from the observation that apparently dissimilar beliefs share fundamental, core characteristics (i.e., contradiction of orthodox scientific understanding of the universe and defiance of conventional understanding of reality). The present paper assessed the supposition that anomalous beliefs were conceptually similar and explicable via common psychological processes by comparing relationships between discrete beliefs (endorsement of urban legends and belief in the paranormal) and cognitive-perceptual personality measures (proneness to reality testing and schizotypy). A sample of 222 volunteers, recruited via convenience sampling, took part in the study. Participants completed a series of self-report measures (Urban Legends Questionnaire, Reality Testing subscale of the Inventory of Personality Organization, Revised Paranormal Belief Scale and the Schizotypal Personality Questionnaire Brief). Preliminary analysis revealed positive correlations between measures. Within schizotypy, the cognitive-perceptual factor was most strongly associated with anomalistic beliefs; disorganised and interpersonal produced only weak and negligible correlations respectively. Further investigation indicated complex relationships between reality testing, the cognitive-perceptual factor of schizotypy and anomalistic beliefs. Specifically, proneness to reality testing deficits explained a greater amount of variance in urban legends, whilst schizotypy accounted for more variance in belief in the paranormal. Consideration of partial correlations supported these conclusions. The relationship between reality testing and urban legends remained significant after controlling for the cognitive-perceptual factor. Contrastingly, the association between the cognitive-perceptual factor and urban legends controlling for reality testing was non-significant. In the case of belief in the paranormal, controlling for proneness to reality testing reduced correlation size, but relationships remained significant. This study demonstrated that anomalistic beliefs vary in nature and composition. Findings indicated that generalised views of anomalistic beliefs provide only limited insight into the complex nature of belief.